Treatment by physical-therapeutic exercises to hemiplegic patient - Leonardo Borrero-González (Universidad de Guantánamo, 2019)
The research is part of the rehabilitation of the hemiplegic older adult, of the right hemibody. A complex of physical therapeutic exercises is presented in order to improve their health, using physical and rehabilitation activities, taking into account the degree of disability in which the patient is. Methods of the theoretical level such as analysis and synthesis, induction and deduction, historical-logical and documentary analysis were used. The observation, interview and survey were used from the empirical level, while the percentage calculation was used from the mathematical statistical level.